A INTER-RELAÇÃO DA CONCORDÂNCIA NOMINAL E DA CONCORDÂNCIA NOS PREDICATIVOS/PARTICÍPIOS PASSIVOS, SOB O ENFOQUE DA TEORIA DA VARIAÇÃO E MUDANÇA LINGÜÍSTICA - Dias, Juçá Fialho; Fernandes, Marisa (Organon, 2012)
This paper intends to examine the relationship between nominalagreement and number agreement in predicative/participle passive, according toFernandes (1996) and Vazzata-Dias (1996), respectively. In this study, we analysethe speech of residents of Florianópolis, investigating two linguistic variables,Formal Paralelism and Phonic Salience, in order to verify, respectively, thehipothesis that plural markers promote plural markers and zero plural markerspromote zero plural markers and that regular plural, because are least distinctive,have lowest probability of agreement. We also investigate three social variables(Sex, age and level of education) in order to verify mainly some indication of stablevariation or linguistic change in progress. The research is conducted throughoutusing the theorical principle of the theory of linguistic variation (Weinreich, Labov& Herzog, 1968, Labov, 1972 and 1994). For quantitative data processing, weused the VARBRUL programs, version 1988/1992.